The TanDEM-X Mission Proposal - Krieger, Gerhard; Moreira, Alberto; Hajnsek, Irena; Werner, Marian; Fiedler, Hauke; Settelmeyer, Eckhard (ISPRS Workshop High-Resolution Earth Imaging for Geospatial Information, 2005)
TanDEM-X is a mission, proposed in 2003 and now in Phase A (feasibility studies) by DLR and EADS Astrium. It is a SAR satellite formation built by the TerraSAR-X and another new TerraSAR-X like add-on satellite to enable single-pass SAR interferometry with variable baselines. The TanDEM-X mission has the goal of generating a global Digital Elevation Model (DEM) with an accuracy corresponding to the HRTI-3 specifications (12 m posting, 2 m relative height accuracy). This paper describes the mission concept and requirements, including several innovative aspects like operation modes, orbit selection and maintenance as well as PRF and phase synchronization. Results from detailed performance estimations show the achievable DEM accuracy. Finally, an overview of the potential of the TanDEM-X mission for several scientific applications is presented.
DLR Import::2019-04-03